Ethical Leadership Influence at Organizations: Evidence from the Field - Demirtas, Ozgur (Journal of business ethics, 2015)
While a number of studies are being done on ethical leadership, little is known about the role of ethical ideology and organizational justice in the relation of the ethical leadership behavior and individual behaviors such as work engagement and organizational misbehavior has tended to be neglected in ethics literature. This study examines the mediating effects of organizational justice on the relations of ethical leadership, work engagement and organizational misbehavior. Also, it investigates the moderating effect of ethical ideology on the relationships among these variables. It proposes that managers’ ethical values and organizational members’ ethical perspectives such as absolutism, exceptionism, situationism, and subjectivism have the potential to be agents of virtue within the organizations. Employee attributions and emotional reactions to the unethical behavior of their leaders are important factors on individual behavior outcomes. So, in this study it is hypothesized that ethical leadership behavior affects organizational justice perception and this, respectively, affects organizational members’ work engagement and organizational misbehavior. It is also hypothesized that ethical ideology would moderate the relationship between the ethical leadership and organizational justice. Results indicate that ethical leadership has both direct and indirect influence on work engagement and organizational misbehavior. Finally, practical implications are discussed, and suggestions for the future research are made.